Study of correlation between bone mineral density and clinical and laboratory indices of rheumatoid arthritis activity - D. A. Gukasyan; R M Balabanova; A V Smirnov; E. L. Nassonov (Научно-практическая ревматология, 2005)
Objective. To study association between bone mineral density (BMD) and clinical and laboratory indices of rheumatoid arthritis (RA) activity Material and methods. 60 women with RA who had not received glucocorticoid and anti-osteoporotic therapy were included. 30 had unchanged menstrual cycle and 30 were postmenopausal. Lumbar spine BMD and proximal femur was studied with double radiological absorptiometry (QDR 1000 Hologic apparatus). W.Wilke indices were used to characterize activity and severity of RA. CRP level was evaluated with quantitative immunoenzyme method. Results. Significant negative association was revealed between spine and femoral neck BMD and RA severity so as between femoral neck BMD and CRP level in pts with unchanged menstrual cycle and in postmenopausal pts.